Adobe InDesign CS5.5 for creating eBooks learn by video - Deuchler, Rufus (Peachpit Press, 2011)
"This innovative product is a focused video workshop and accompanying 48-page full-color book that will teach InDesign users how to design documents with e-book publishing in mind, and create and publish them in the ePub format. Viewers will learn about new electronic publishing features in InDesign CS5.5, how to work with text, create hyperlinks and cross-references, work with graphics, create covers and tables of contents, and export to the ePub format. How to fine-tune ePub code will be covered, and an appendix will provide an introduction to the ePub format. Experienced instructor Rufus Deuchler presents three hours of exceptional quality video tutorials, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside in InDesign. Project files used in the lessons are included on the disc so viewers can practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page
Keywords: Adobe InDesign (Electronic resource); Electronic publishing -- Computer programs; Self-publishing; Livres numériques; Édition à compte d'auteur; Electronic publishing; Computer programs